Exploring the Classification Accuracy of the Early Communication Indicator (ECI) With Dual-Language Learners From Latinx Backgrounds. (September 2022) - King, Marika; Larson, Anne L.; Buzhardt, Jay
Few, if any, reliable and valid screening tools exist to identify language delay in young Spanish–English speaking dual-language learners (DLLs). The early communication indicator (ECI) is a brief, naturalistic measure of expressive communication development designed to inform intervention decision-making and progress monitoring for infants and toddlers at-risk for language delays. We assessed the accuracy of the ECI as a language-screening tool for DLLs from Latinx backgrounds by completing classification accuracy analysis on 39 participants who completed the ECI and a widely used standardized reference, the Preschool Language Scales, Fifth Edition–Spanish, (PLS-5 Spanish). Sensitivity of the ECI was high, but the specificity was low, resulting in low classification accuracy overall. Given the limitations of using standalone assessments as a reference for DLLs, a subset of participants ( n = 22) completed additional parent-report measures related to identification of language delay. Combining the ECI with parent-report data, the specificity of the ECI remained high, and the sensitivity improved. Findings show preliminary support for the ECI as a language-screening tool, especially when combined with other information sources, and highlight the need for validated language assessment for DLLs from Latinx backgrounds.